2015
DOI: 10.3390/nu7031817
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dietary Allergen Exclusion Therapy on Eosinophilic Colitis in Chinese Infants and Young Children ≤ 3 Years of Age

Abstract: Eosinophilic colitis is a well recognized clinical entity mainly associated with food allergies. Empiric treatment options include dietary allergen exclusion (extensively hydrolyzed protein formula and elimination diet), anti-allergy medications (antihistamines and leukotriene receptor antagonists) and corticosteroids. We evaluated the effectiveness of dietary antigen exclusion on clinical remission of eosinophilic colitis in infants and young children. We retrospectively reviewed charts of all infants and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The IgE concentration associated with allergen stimulation does not reflect the tissue concentration at the location of the ongoing allergic inflammation. This suggests that most of the eosinophilic inflammation in the colon is associated with an IgE-independent mechanism [ 49 ]. The diagnosis is established by the presence of an increased eosinophilic infiltrate in the colon wall in symptomatic patients.…”
Section: Clinical Features Of Non-ige Gastrointestinal Famentioning
confidence: 99%
“…The IgE concentration associated with allergen stimulation does not reflect the tissue concentration at the location of the ongoing allergic inflammation. This suggests that most of the eosinophilic inflammation in the colon is associated with an IgE-independent mechanism [ 49 ]. The diagnosis is established by the presence of an increased eosinophilic infiltrate in the colon wall in symptomatic patients.…”
Section: Clinical Features Of Non-ige Gastrointestinal Famentioning
confidence: 99%
“…In one study, forty-nine children were identified with eosinophilic colitis. Elemental formula, simple elimination diet (elemental formula for infants who were on formula feeding or dietary elimination of milk, egg, peanut and wheat for those who were not on formula feeding) or combination therapy resulted in clinical improvement in 75%, 88.2% and 80% of patients, respectively [ 17 ]. In a study by Stamm et al the use of a strict elemental diet for 3 months prior to endoscopy was not associated with a decreased frequency of eosinophilic inflammation in any tissue, which did not match the results of our study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding CMA in EGIDs are minimal and likely to reflect the lack of clarity regarding the diagnostic criteria largely resulting from a paucity of normative reference values for eosinophil counts in the GI tract. There are reports about the improvement of EGIDs by elimination of CM (see specific comorbidities and (57–63)). It is outside the remit of this paper to describe EGIDs in any more detail and their diagnosis and management is well reviewed in other articles (64,65).…”
Section: Clinical Gastro‐intestinal Presentation Of Cmamentioning
confidence: 99%